(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzed the innovation of the mechanical engineering enterprises of Ukraine, investigated the dynamics of innovation activity, trends and the scope of funding of costs for innovation, noted the general trends for innovation activities by type of activity. The sources of funding of the innovation were investigated in order to a comprehensive analysis of indicators of innovation activity, namely the share of own funds, resources that are allocated from the state budget and off-budget funds, domestic and foreign investors, credit money. Also, the effectiveness of innovative enterprises under the conditions of implementation of the Framework Programme (‘HORIZON 2020’, ‘Manufuture’, ‘Factories of the Future’) was analyzed. The main prospects for the development of innovative mechanical engineering enterprises were defined.